A Bayesian Approach to the Estimation of Environmental Kuznets Curves for CO2 Emissions - Massimiliano Mazzanti; Antonio Musolesi; Roberto Zoboli (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper investigates the EKC curves for CO2 emissions in a panel of 109 countries during the period 1959-2001. The length of the series makes the application of a heterogeneous estimator suitable from an econometric point of view. The results, based on the hierarchical Bayes estimator, show that different EKC dynamics are associated with the different sub samples of countries considered. On average, more industrialized countries show an EKC evidence in quadratic specifications, which are nevertheless probably evolving into an N shape, emerging from cubic specifications. Less developed countries consistently show that CO2 emissions still rise positively with income, though some signals of an EKC path arise.
Keywords: C23; Q25; 330; Environmental Kuznets Curve; CO2 Emissions; Bayesian Approach; Heterogeneous Panels; Environmental Kuznets Curve; Umweltbelastung; Wirtschaftswachstum; Kohlendioxid; Bayes-Statistik; Welt